Rectangular Patch Antenna Array for Radar Application - Yudi Yuliyus Maulana; Yuyu Wahyu; Folin Oktafiani; Yussi Perdana Saputra; Arie Setiawan (Universitas Ahmad Dahlan, 2016)
This paper deals with the characterization of Rectangular Patch Antenna Arrays numerically and experimentally. This antenna is designed to work around frequency of 9.4GHz for radar applications. In the design process, the Computer Simulation Technology (CST) simulator software is utilized to determine the value of the antenna parameters such as gain, radiation pattern, and voltage standing wave ratio (VSWR). The Rectangular Patch Antenna Arrays realized by using the 1x16 patch antenna array, while the patch antenna is implemented using microstrip lines. The Duroid/RT5880 substrate with a dielectric constant of 2.2 and a thickness of 1.57mm applied for implementation. The characterization results show that the VSWR of realized antenna is 1.052, and the gain is 15,26dB which is 1.4dB lower than the design result, while the radiation pattern is unidirectional and elliptical polarization.